Calorie Restriction Decreases Murine and Human Pancreatic Tumor Cell Growth, Nuclear Factor-κB Activation, and Inflammation-Related Gene Expression in an Insulin-like Growth Factor-1−Dependent Manner - Harvey, Alison E.; Lashinger, Laura M.; Hays, Drew; Harrison, Lauren M.; Lewis, Kimberly; Fischer, Susan M.; Hursting, Stephen D. (PLOS ONE, 2014)
Calorie restriction (CR) prevents obesity and has potent anticancer effects that may be mediated through its ability to reduce serum growth and inflammatory factors, particularly insulin-like growth factor (IGF)-1 and protumorigenic cytokines. IGF-1 is a nutrient-responsive growth factor that activates the inflammatory regulator nuclear factor (NF)-κB, which is linked to many types of cancers, including pancreatic cancer. We hypothesized that CR would inhibit pancreatic tumor growth through modulation of IGF-1-stimulated NF-κB activation and protumorigenic gene expression. To test this, 30 male C57BL/6 mice were randomized to either a control diet consumed ad libitum or a 30% CR diet administered in daily aliquots for 21 weeks, then were subcutaneously injected with syngeneic mouse pancreatic cancer cells (Panc02) and tumor growth was monitored for 5 weeks. Relative to controls, CR mice weighed less and had decreased serum IGF-1 levels and smaller tumors. Also, CR tumors demonstrated a 70% decrease in the expression of genes encoding the pro-inflammatory factors S100a9 and F4/80, and a 56% decrease in the macrophage chemoattractant, Ccl2. Similar CR effects on tumor growth and NF-κB-related gene expression were observed in a separate study of transplanted MiaPaCa-2 human pancreatic tumor cell growth in nude mice. In vitro analyses in Panc02 cells showed that IGF-1 treatment promoted NF-κB nuclear localization, increased DNA-binding of p65 and transcriptional activation, and increased expression of NF-κB downstream genes. Finally, the IGF-1-induced increase in expression of genes downstream of NF-κB (Ccdn1, Vegf, Birc5, and Ptgs2) was decreased significantly in the context of silenced p65. These findings suggest that the inhibitory effects of CR on Panc02 pancreatic tumor growth are associated with reduced IGF-1-dependent NF-κB activation.